Identification of Macrophage Extracellular Trap-Like Structures in Mammary Gland Adipose Tissue: A Preliminary Study - Mohanan, Sunish; Horibata, Sachi; McElwee, John L.; Dannenberg, Andrew J.; Coonrod, Scott A. (Frontiers in Immunology, 2013)
PAD4-mediated hypercitrullination of histone H4 arginine 3 (H4R3) has been previously found to promote the formation of Neutrophil Extracellular Traps in inflamed tissues and the resulting histone H4 citrulline 3 (H4Cit3) modification is thought to play a key role in extracellular trap (ET) formation by promoting chromatin decondensation. In addition to neutrophils, macrophages have also recently been found to generate functional extracellular traps (METs). However, a role for PADs in ET formation in macrophages has not been previously described. Transcripts for PAD2 and PAD4 are found in mature macrophages and these cells can be induced to citrullinate proteins, thus raising the possibility that PADs may play a direct role in ET formation in macrophages via histone hypercitrullination. In breast and visceral white adipose tissue from obese patients, infiltrating macrophages are often seen to surround dead adipocytes forming characteristic “crown-like structures” (CLS) and the presence of these lesions is associated with increased levels of inflammatory mediators. In light of these observations, we have initiated studies to test whether PADs are expressed in CLS macrophages and whether these macrophages might form METs. Our preliminary findings show that PAD2 (and to a lesser extent, PAD4) is expressed in both in the macrophage cell line (RAW 264.7) and in CLS lesions. Additionally, we provide evidence that macrophage-derived extracellular histones are seen around presumptive macrophages within CLS lesions and that these histones contain the H4Cit3 modification. These initial findings support our hypothesis that obesity-induced adipose tissue inflammation promotes the formation of METs within CLS lesions via PAD-mediated histone hypercitrullination. Subsequent studies are underway to further validate these findings and to investigate the role in PAD-mediated MET formation in CLS function in the mammary gland.